Development of a national and secure automated management system for accommodation facilities in Uzbekistan - Mukhamadalieva Nodira Begim Daminjonovna; Zhuraeva Nargiza Abduvogidovna, (European Journal of Life Safety and Stability (2660-9630), 2021)
Currently, a process of radical reform of the tourism industry has been launched in Uzbekistan. Its goal is to transform tourism into a strategic direction for the development of the national economy, which will ensure its diversification and accelerated development of the regions. This article discusses ACS for the hospitality business, especially OPERA and 1C, as well as the development of a national product for the accommodation facility in the regions. Comparative analysis is used as a research method. For the analysis, primary data were used, which were collected by the survey method.